The effect of mepolizumab dosage form on treatment outcomes in severe asthma - Vetchá, Martina; Kubová, Kateřina; Glynos, Constantinos; Pavloková, Sylvie; Krčmová, Irena; Voláková, Eva; Fibigr, Ondřej; Hutyrová, Beáta; Vlachová, Alena; Zeman, Jiří; Vetchý, David (Frontiers in Medicine, 2025)
BackgroundA monoclonal antibody such as mepolizumab typically first appears as a parenteral lyophilized formulation (LYO), then as various parenteral solution forms, and finally as a self-administered form at homecare. While more studies compare mepolizumab safety and efficacy across dosage forms, no data exists on the impact of switching to more successive dosage forms in real-world settings. This study aims to assess clinical outcomes in patients from five national Czech asthma centers who were switched from the LYO to the liquid formulation and then to home self-administration.MethodsMepolizumab was administered in three phases: LYO for 6–9 months, followed by prefilled syringes (PFS) or autoinjectors (AI) in hospitals for 6–9 months, and finally, liquid forms at homecare for another 6–9 months. Data collected included age, BMI, nasal polyposis (NP), gastroesophageal reflux (GERD), and other comorbidities. The results were statistically evaluated using exacerbation rate (ER), asthma control test, forced expiratory volume, blood eosinophil count, and required systemic oral corticosteroid (OCS) daily dose.ResultsThree months after initiation of administration, all methods showed improvement compared to the values at the beginning of treatment, with ER decreasing from a median of 4 to 0. Similarly, the median OCS decreased from 5 mg to 0 mg across all methods throughout the treatment. A more significant OCS dose reduction was observed in patients with NP (87.5% vs. 50%) and GERD (70% vs. 50%), who typically require higher OCS doses to achieve asthma control. AI/PFS outperformed LYO in ER (97.5–100% vs. 50–100% after 6–9 months of treatment) and OCS reduction (50–100% vs. 31.2–100% after 6–9 months of treatment), which was influenced rather by the later usage of AI/PFS and thus longer overall treatment times than the administrating method.ConclusionMepolizumab improved real-life clinical outcomes in patients with severe asthma, regardless of the dosage forms or homecare settings.